2017
DOI: 10.1002/cem.2910
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of HILIC retention behavior with theoretical models and new spline interpolation technique

Abstract: When it is taken into account that hydrophilic interaction liquid chromatography (HILIC) as an analytical method is relatively young compared with the other techniques, retention modeling could still bring scientifically valuable data to the field. Therefore, in this paper, olanzapine and its 8 impurities were selected as a test mixture, considering that they have never been analyzed in HILIC before. Their investigation on 4 different HILIC columns (bare silica, cyanopropyl, diol and zwitterionic) has been per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In all cases, DoE experiments are for HPLC method fine-tuning, previously reported methods or preliminary experiments being the starting point. Numerous reverse phase HPLC methods optimized using AQbD are published, but there are several using gradient HILIC (hydrophilic interaction chromato graphy) methods as well (53). Using isocratic HPLC methods, the most frequent CMPs are the aforementioned input variables (54,55).…”
Section: Quality-by-design In the Development Of Analytical Methods And Pharmaceutical Manufacturingmentioning
confidence: 99%
“…In all cases, DoE experiments are for HPLC method fine-tuning, previously reported methods or preliminary experiments being the starting point. Numerous reverse phase HPLC methods optimized using AQbD are published, but there are several using gradient HILIC (hydrophilic interaction chromato graphy) methods as well (53). Using isocratic HPLC methods, the most frequent CMPs are the aforementioned input variables (54,55).…”
Section: Quality-by-design In the Development Of Analytical Methods And Pharmaceutical Manufacturingmentioning
confidence: 99%
“…For that reason, Tumpa et al. divided the experimental space into different segments with an interpolated polynomial for each part, which is known as spline interpolation [157]. The MM, Q, ADS, and LSS model were tested in this study.…”
Section: Methodsmentioning
confidence: 99%
“…To enhance the accuracy of retention models in HILIC, Tumpa et al 137 have demonstrated the construction of polynomial models using a spline interpolation technique based on olanzapine and its impurities on various HILIC stationary phases. High Q 2 values indicated the good predictive ability of the polynomial equations, with the most accurate model giving errors of prediction below 10% over all studied HILIC systems in comparison to the LSSM, adsorption, mixed-mode, and quadratic models.…”
Section: ■ Prediction Of Retention In Hilicmentioning
confidence: 99%
“…The experimental data describing the relationship of ln k versus φ fit quite well to a quadratic relationship (eq ). The mixed-mode model (eq ), which combines eq and eq by considering both partitioning and adsorption mechanisms is more suitable to describe HILIC retention than linear models over a wider φ range. where c 1 expresses the interaction between analytes and the SP and c 2 the interaction between analytes and MP solvents.…”
Section: Prediction Of Retention In Hilicmentioning
confidence: 99%
See 1 more Smart Citation